Influence of low-dose ketamine on periodic and aperiodic components of resting-state EEG dynamics (Student Conference Proceedings, 2025)
Ketamine, an NMDA receptor antagonist, has garnered interest for scientific use due to its unique effects on brain dynamics. Previous research has demonstrated that ketamine reduces the alpha peak power and shifts the excitation inhibition balance (E:I balance) toward excitation when administered in anaesthetic dosages. This study investigates the effects of low-dose ketamine on resting-state EEG dynamics, focusing on these two findings. Using a crossover design, participants received ketamine, propofol, or a placebo. The 1/f-like aperiodic component of the spectrum was analyzed to assess changes in the E:I balance. Results showed a significant decrease in alpha peak power and a reduction in the exponents of the 1/f spectrum in the ketamine condition, indicating a shift toward excitation in the E:I balance. These findings are consistent with the previous research on narcotic dosages and suggest that even at low doses, ketamine induces measurable alterations in brain activity. It should be noted that the current data collection is still ongoing, but these preliminary results already underscore the potential of ketamine in probing NMDA receptor hypofunction and E:I balance in cognitive and behavioral contexts.
Keywords: Sensor Data Analysis; electroencephalogram